Victoria vel Victorina and Her Career Across the Centuries in Early Modern and Modern Numismatic Literature. A Case Study on the Reception of Ancient Culture - Kluczek, Agata A. (Polskie Towarzystwo Filologiczne, 2018)
The article recalls what was established by researchers in reference to Victoria, the mother of emperor Victorinus, and mentioned in the ancient literary sources, the Liber de Caesaribus by Aurelius Victor and the Historia Augusta. These works present Victoria, augusta and mater castrorum, as a woman who was politically engaged in the events in the Imperium Galliarum in the 3rd century. The ancient tradition exerted an influence upon the modern authors of the numismatic corpora. Above all the remark of an early scriptor about coins issued with a portrait of Victoria on them proved particularly inspiring. By taking her as a point of departure, but also by engaging creatively with the details of Victoria’s biography which emerge from the reading of ancient texts, the early modern writers created the figure of Victorina in their works. She was supposed to issue her own coins, but she was also commemorated on various monetary types and honoured by consecration coins.
Keywords: Victoria, the mother of emperor Victorinus; coins